Factor, simplify, and then do u-substitution to avoid mechanical errors.
[math]f(x) = y = \sin(x) \cos^3(x) - \sin^3(x) \cos(x) = \\
\sin(x) \cos(x) \{\cos^2(x) - \sin^2 (x) \} =\\
u(\cos^2 (x) - \{1 - \cos^2 (x) \} ) =\\
u(2 \cos^2 (x) - 1) = uv \implies \\
y’ = uv’ + u’v.[/math]
That was not too hard.
[math] u = \sin (x) \cos (x) \implies\\
u’ = \sin (x) \{ - \sin (x)\} + \cos (x) \cos (x) = \cos^2 (x) - \sin^2 (x) = 2 \cos^2 (x) - 1.[/math]
Basic, but you may notice that [imath]u’ = v[/imath]. Weird but very interesting.
[math]v = \cos^2(x) - 1 \implies v’ = 2 \cos (x) \{- \sin(x) \} = -2u.[/math]
Weirder and weirder (unless I screwed up somewhere).
[math]\therefore y’ = uv’ + u’v = - 2u^2 + v^2.\\
\therefore y’ = 0 \implies v^2 = 2u^2.[/math]
Check all that. If it is correct, keep on trucking by reducing everything to cosines. I suspect you will need another substitution at the end.